Avaliação in vitro da atividade antifúngica do fosfato dissódico de dexametasona frente à cepas de Candida albicans resistentes ao fluconazol e sua atividade contra biofilme - Silva, Lisandra Juvêncio da (2021)
Much has been discussed recently about fungal infections superficial and thorough has increased significantly and such as consequence end up cause increase of rates of morbidity and mortality of individuals nowadays although increase development of antibiotics, arsenal antifungals found for market for the treatment of fungal infection still low, as soon end up limiting patient’s treatment and may cause resistance to strains. Species of the genus Candida are the most common opportunistic agents in candidiasis-related fungal infections in species in different groups of immunodeficiency patients. Therefore, drug redirection is an important means of prospecting for new therapeutic alternatives, as these drugs have well-characterized pharmacological and toxicological properties, thus reducing the time and cost of drug development. The present study investigates the antifungal action of dexamethasone sodium phosphate (DEXA), a type of glucocorticoid whose main pharmacological actions include anti-inflammatory, anti-allergic, and anti-rheumatic. Sensitivity tests were carried out using the broth microdilution method (CLSI; M27-A3) and the checkerboard technique applied to mature and developing biofilms of two strains of C. albicans, along with the hyphal production test and analysis of the mechanism of cell death through flow cytometry. The results showed activity of dexamethasone phosphate (DEXA) against strains resistant to fluconazole (FLU), with minimum inhibitory concentrations (MIC) varying from 31.25 to 500 μg/mL, while DEXA and FLU together had a synergistic effect, causing 100% inhibition of all strains in relation to the developing biofilm. In turn, DEXA alone reduced the cell viability of the developing biofilm by 89%, while the mature biofilm showed no reduction when treated with DEXA alone or in combination with FLU. The combination also caused a decrease in the production of hyphae and changes in the level of mitochondrial depolarization, an increase in the generation of reactive oxygen species, and an increase in the externalization of phosphatidylserine. In addition, it DEXA interacted with ALS3 and SAP5, important in virulence processes. Dexamethasone disodium phosphate showed antifungal activity against strains of Candida albicans resistant to fluconazole and caused a decrease in the production of hyphae, so it can be considered a potential drug to help fight fungal infections caused by Candida albicans.